MiR-92b-3p Exerts Neuroprotective Effects on Ischemia/Reperfusion-Induced Cerebral Injury via Targeting NOX4 in a Rat Model. (30th March 2022) - Huang, Yongpan; Tang, Jiayu; Li, Xiaojuan; Long, Xian; Huang, Yansong; Zhang, Xi
Abstract : The necessity to increase the efficiency of organ preservation has pushed researchers to consider the mechanisms to minimize cerebral ischemia/reperfusion (I/R) injury. Hence, we evaluated the role of the miR-92b-3p/NOX4 pathway in cerebral I/R injury. A cerebral I/R injury model was established by blocking the left middle cerebral artery for 2 h and reperfusion for 24 h, and a hypoxia/reoxygenation (H/R) model was established. Thereafter, cerebral I/R increased obvious neurobiological function and brain injury (such as cerebral infarction, apoptosis, and cell morphology changes). In addition, we noted a significant decrease in the expression of miR-92b-3p, as well as increases in apoptosis and oxidative stress and an increase in NOX4. Furthermore, overexpression of miR-92b-3p blocked the inhibitory effect of miR-92b-3p on the expression of NOX4 and the accumulation of oxygen-free radicals. Bioinformatics analysis found that NOX4 may be the target gene regulated by miR-92b-3p. In conclusion, the involvement of the miR-92b-3p/NOX4 pathway ameliorated cerebral I/R injury through the prevention of apoptosis and oxidative stress. The miR-92b-3p/NOX4 pathway could be considered a potential therapeutic target to alleviate cerebral I/R injury.